Spatial and temporal variability of cv. Tempranillo response within the Toro DO (Spain) and projected changes under climate change - Maria C. Ramos; Daniël T.H.C. Go; Santiago Castro (OENO One, 2021)
The aim of this work was to analyse the spatial and temporal variability of the response of Tempranillo variety within the Toro Designation of Origin and the potential changes under climate change scenarios. Phenology (bud break, bloom, veraison and maturity) and grape acidity recorded in plots located at seven locations in the DO, at elevations between 670 and 799 m above the sea level (a.s.l.), were analysed. Changes in phenology and composition were projected for two climate change emission scenarios (Representative Concentration Pathways RCP4.5 and RCP8.5) considering the predicted changes in climate variables using an ensemble of models.  During the analysed period, variations in the phenological timing higher than 20 days were recorded, and acidity varied between 4 and 8 gL-1. The variability in phenology and grape acidity was mainly driven by temperature and available water in different periods between phenological stages, although the effect of soil properties was also confirmed. An advance of all phenological phases (up to 6, 6, 8 and 12 days under the RCP4.5 scenario by 2050 and near double under the RCP8.5 scenario) were projected, as well as a decrease in acidity of up to 0.9 gL-1. The results were in agreement with the variability observed in years with contrasting weather conditions.